Association between peripheral blood serum phenylalanine to tyrosine ratio and the risk of moyamoya disease: a case-control study - Shixiong Lei; Shixiong Lei; Mengnan Wang; Mengnan Wang; Jiali Pan; Daming Wang; Peicong Ge; Peicong Ge; Dong Zhang (Frontiers in Neurology)
Background and aimsPhenylalanine (Phe) and its metabolite tyrosine (Tyr) have been shown to play an important role in the mechanisms and development of cardiovascular and cerebrovascular disease, and its ratio (Phe/Tyr) has been suggested to be an important indicator of inflammation. It was uncertain whether Phe/Tyr is associated with higher risk of MMD. Therefore, we conducted this study to evaluate the relationship between Phe/Tyr and the risk of MMD and its subtypes.MethodsA total of 360 adult MMD patients and 89 age-matched healthy controls (HCs) were consecutively recruited for this prospective study. We measured peripheral blood serum Phe and Tyr levels in all participants to analyze the association between Phe/Tyr and the risk of MMD and its subtypes.ResultsSerum Phe/Tyr was significantly higher in MMD patients and their subtypes than in HCs (p < 0.01). After adjusting for traditional risk factors, Phe/Tyr was positively associated with the risk of MMD (OR: 14.035, 95%CI: 2.784–70.748, p = 0.001). When Phe/Tyr was assessed in quartile subgroups, the third quartile (Q3) and fourth quartile (Q4) subgroups of Phe/Tyr had a significantly increased risk of MMD compared to the first quartile (Q3, OR: 2.019, 95%CI: 1.066–3.824, p = 0.031; Q4, OR: 2.887, 95%CI: 1.446–5.765, p = 0.003). The risk of MMD subtypes also increased with elevated Phe/Tyr level. Meanwhile, the addition of Phe/Tyr to conventional risk factors could significantly improve the risk prediction for MMD.ConclusionIn this study, the risk of MMD increased with elevated Phe/Tyr, suggesting that peripheral blood serum Phe/Tyr may be a valuable predictive biomarker of adult MMD.